Joint Ventures in Yugoslavia: Opportunities and Constraints - Artisien, Patrick F. R.; Buckley, Peter J. (Journal of International Business Studies, 1985)
Yugoslavia's post-1965 economic policies have been directed towards opening the economy to foreign trade and encouraging inward investment in Joint Ventures. This research examines the opportunities and constraints facing Western multinational companies which invest in Joint Ventures in Yugoslav industry. The empirical evidence drawn from a sample of 42 West European and North American companies addresses itself to the formation and success of Joint Ventures, the route to foreign direct investment in Yugoslavia and motives and preferences for Joint Ventures to other forms of industrial cooperation.